Kualitas Pelayanan Telephone Operator Pada Front Office Departemen di Kima Bajo Resort & SPA Manado - Michael Rawung; Richard Poluan; Seprin Pareda (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
Quality Service Telephone Operator implementation is quite good, but in some dimensions of service indicators are still not satisfactory in serving guests or customers who visit and stay . The lack of speed in serving guests so that guests wait long to be serve, guests often have to try and repeat phone calls to get a response from officers operators in this case guests do not feel the comfort and satisfaction with the services provided by staff. The qualitative method used to examine the condition of natural objects, where the researcher as the key instrument and using data collection by observation, interviews and document research. In terms of responsiveness is still lacking due to the lack of speed in serving guests who need assistance. So is the form of direct services that there are still obstacles in communication , technical issues weak telecommunications network is the main thing for in hibitor maximum service. From these results it can be concluded that should be directed to improving the quality of service to guests or customers .